Comparative assessment of the role of TMPRSS2 and ACE-2 receptors in the development of olfactory disorders in infection with coronavirus SARS-CoV-2 - Usova, O.M. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Today, evidence of the impact of the SARSCoV-2 coronavirus not only on the cells of the olfactory epithelium, but also on the components of the deeper parts of the olfactory system (olfactory bulbs and the olfactory area of the cerebral cortex), indicates the expression of proteins by the cells of the olfactory epithelium that contribute to further penetration of the virus. An urgent problem is the lack of comprehensive studies of the role of morphological and immunological features of various parts of the olfactory system in the occurrence of olfactory disorders and insufficient understanding of the relationship between their duration and the localization of cells affected by the SARS-CoV-2 coronavirus. The оbjective of the study is to clarify the feasibility of studying the role of TMPRSS2 receptors and comparing it with the role of ACE-2 receptors localized on the components of the olfactory epithelium in the development of olfactory disorders in the Coronavirus Disease 2019 caused by SARS-CoV-2. Methods. This study was performed using autopsy material, namely fragments of the mucous membrane of the upper parts of the nasal cavity (olfactory epithelium), obtained from 10 deceased (6 women and 4 men) aged 53 to 79 years with a laboratory-confirmed diagnosis of "Coronavirus Disease 2019" (polymerase chain reaction) and olfactory disorders of various degrees in the anamnesis. Mucosal samples were stained both with hematoxylin and eosin, and using an immunohistochemical method with antibodies to transmembrane serine protease-2 (TMPRSS2) and angiotensin-converting enzyme (ACE-2). Results. As a result of this study, the number of OMP-positive cells in sections of the olfactory epithelium was on average 46.5 in the field of view at 200x magnification (35.0-59.0), ACE-2-positive cells - 38.5 in the field of view at magnification 200x (21.0-55.0), TMPRSS2-positive - 81 in the field of view at 200x magnification (63.0-96.0). Conclusion. Studying the role of TMPRSS2 and ACE-2 receptors localized on olfactory epithelial cells in the development of olfactory disorders in the 2019 coronavirus disease caused by SARS-CoV-2 will provide a better scientific understanding of the development of disease-specific symptoms.